2018
DOI: 10.48550/arxiv.1808.09378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Option pricing models without probability: a rough paths approach

Abstract: We describe the pricing and hedging practices refraining from the use of probability. We encode volatility in an enhancement of the price trajectory and we give pathwise presentations of the fundamental equations of Mathematical Finance. In particular this allows us to assess model misspecification, generalising the so-called fundamental theorem of derivative trading (see Ellersgaard et al. [EJP17]). Our pathwise integrals and equations exhibit the role of Greeks beyond the leading-order Delta, and makes expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In a pricing and hedging context there is an even more compelling reason to use signatures as a feature map for the time series: Not only does a signature-based generation yield a faster training and more stable convergence, but in a pricing and hedging context it eliminates pricing ambiguities while pure returns-based generation does not as Brigo explains in [9] in a framework consistent with statistical analysis of historical volatility that can lead to arbitrarily different options prices. Previously, [2,9] had shown that implied volatility is linked with a purely pathwise lift of the stock dynamics, confirming the idea that while historical volatility is a statistical quantity, implied volatility is a pathwise one. See also the end of Section 2.2.1 for a hedging perspective.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…In a pricing and hedging context there is an even more compelling reason to use signatures as a feature map for the time series: Not only does a signature-based generation yield a faster training and more stable convergence, but in a pricing and hedging context it eliminates pricing ambiguities while pure returns-based generation does not as Brigo explains in [9] in a framework consistent with statistical analysis of historical volatility that can lead to arbitrarily different options prices. Previously, [2,9] had shown that implied volatility is linked with a purely pathwise lift of the stock dynamics, confirming the idea that while historical volatility is a statistical quantity, implied volatility is a pathwise one. See also the end of Section 2.2.1 for a hedging perspective.…”
mentioning
confidence: 80%
“…In fact, this test is based on a notion that is reminiscent of the role of moment generating functions on path space and hence characterises the distribution of the stochastic process uniquely, see Appendix A for details. Furthermore, it follows from [2,46], that in addition to the advantages above, signatures also provide the right framework to match hedging objectives and hence to bypass matter (4).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning recent lines of mathematical finance such as Armstrong, Bellani, Brigo, & Cass (2018) and Brigo (2019), which also place focus on probability-free frameworks, but these articles address more general questions than here, relating to pricing and hedging in the absence of such a measure, and depend upon rough path theory. Although we all target probability-free interpretations of existing results (for example Ellersgaard, Jönsson, & Poulsen (2017) in their case) and derivations of new ones, the underlying mathematics is ultimately very different.…”
Section: Related Literaturementioning
confidence: 99%
“…This appears to be a significant advantage compared to the classical notions of pathwise stochastic integration in [Bic81, WT89, Kar95, Nut12], which do not come with such stability estimates. In particular, the pathwise stability results of rough path theory allow one to prove a model-free version of the so-called fundamental theorem of derivative trading-see [ABBC18]-and may be of interest when investigating discretization errors of continuous-time trading in model-free finance; see [Rig16]. Furthermore, in contrast to Föllmer integration, rough integration allows one to consider general functionally generated integrands g(S t ), where g is a general (sufficiently smooth) function g: R d → R d , and not necessarily the gradient of another vector field f : R d → R. For instance, model-free portfolio theory constitutes a research direction in which it is beneficial to consider non-gradient trading strategies; see [ACLP21].…”
Section: Introductionmentioning
confidence: 99%